2015
DOI: 10.1080/15299716.2014.994159
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Measuring Posttraumatic Stress Disorder in Bisexuals Using the PTSD Checklist–Civilian Version (PCL-C)

Abstract: Research suggests an elevated level of posttraumatic stress disorder (PTSD) among bisexuals. The PTSD Checklist-Civilian version (PCL-C) is a self-report measure used to assess PTSD symptoms in nonmilitary persons, closely following Diagnostic and StatisticalManual of Mental Disorders ( DSM-IV) criteria. In a study of 405 bisexuals in Ontario, Canada, the authors evaluated the PCL-C using confirmatory factor analysis and found it performed poorly. The authors caution researchers to be aware of the PCL-C's limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The PCL-C has been used with sexual minority women with potentially traumatic events exposure (Dworkin et al, 2018). Given that Macleod, Bauer, MacKay, Robinson, and Ross (2015) found issues with the PCL-C among bisexual respondents, we assessed whether this measure was reliable among this subgroup, as this was our biggest identity group in the sample, and found adequate reliability (␣ ϭ .73). A total score was computed by summing the items, and higher total scale scores represented greater self-reported PTSD symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The PCL-C has been used with sexual minority women with potentially traumatic events exposure (Dworkin et al, 2018). Given that Macleod, Bauer, MacKay, Robinson, and Ross (2015) found issues with the PCL-C among bisexual respondents, we assessed whether this measure was reliable among this subgroup, as this was our biggest identity group in the sample, and found adequate reliability (␣ ϭ .73). A total score was computed by summing the items, and higher total scale scores represented greater self-reported PTSD symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Although an earlier study raised some concern about the use of the previous version of the PCL (i.e., the PCL-Civilian Version for DSM–IV ) with bisexual participants (MacLeod, Bauer, Mackay, Robinson, & Ross, 2015), the PCL-5 (for DSM–5 ) is likely a more valid measure of PTSD symptoms. MacLeod and colleagues (2015) noted that, in their factor analysis with bisexual participants, the avoidance/numbing cluster performed poorly. However, in the PCL-5 , avoidance and numbing symptoms are separated and load onto different factors to reflect the change from a three to four-factor conceptualization of PTSD symptoms in DSM–5 .…”
Section: Methodsmentioning
confidence: 99%
“…Boal and colleagues (2017) found that this scale is valid in an online, self-administered format. Although no validation study focused on sexual minorities was found, ample studies have studied sexual minorities using the PTSD Checklist (e.g., Dworkin et al, 2018; MacLeod et al, 2015; Pinciotti & Orcutt, 2021; Smith et al, 2016).…”
Section: Methodsmentioning
confidence: 99%